2022
DOI: 10.3389/fonc.2022.945143
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and diagnostic value of circRNA expression in prostate cancer: A systematic review and meta-analysis

Abstract: BackgroundCircular RNAs (circRNAs) are receiving increasing attention as novel biomarkers. Our goal was to investigate the diagnostic, clinicopathological, and prognostic utility of circRNAs in prostate cancer (PCa).MethodsRelevant literature was searched in PubMed, Web of Science, and EMBASE. Sensitivity, specificity, diagnostic odds ratio (DOR), negative likelihood ratio (NLR), positive likelihood ratio (PLR), and the area under the curve (AUC) were calculated to evaluate the diagnostic accuracy of circRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that circRNAs play an important role in their occurrence and have become a research hotspot. [3][4][5] circRNA plasmacytoma variant translocation 1 (circPVT1), transcribed from the long noncoding RNA region with PVT1 locus on chromosome 8q24, is upregulated to drive the development of various cancers. 6,7 PVT1 from online data analysis was abnormally expressed in BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that circRNAs play an important role in their occurrence and have become a research hotspot. [3][4][5] circRNA plasmacytoma variant translocation 1 (circPVT1), transcribed from the long noncoding RNA region with PVT1 locus on chromosome 8q24, is upregulated to drive the development of various cancers. 6,7 PVT1 from online data analysis was abnormally expressed in BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first isolation from mosquitoes in Hainan Province, China in 1964, it has broken out and become prevalent in 17 provinces and cities (Zhai et al, 2008). So far, the virus RNA or antibodies have been detected in horses, pigs, cattle, sheep, blue foxes, kangaroos, monkeys, red pandas, and some poultry (Nemoto et al, 2015;Li et al, , 2019Yang et al, 2018;Ren et al, 2020;Xing et al, 2020;Rattanatumhi et al, 2022;Shi et al, 2022a;Zhao et al, 2022). Of particular note is that neutralizing antibodies against GETV have been found in human serum in Malaysia, Australia, and China (Zhai et al, 2008;Shi et al, 2022b), and the specific antibody titers in febrile populations are significantly higher than in healthy populations, indicating that GETV infection is related to human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs, which act as miRNA sponges, adsorb miRNAs and further regulate the expression of mRNAs, which is the most studied function of circRNAs (Hansen et al, 2013). circRNA-miRNA-mRNA has been proven to play an important role in chronic diseases such as cancer, brain tissue disease, and vascular disease (Wang et al, 2021;Zhu et al, 2021;Xie et al, 2022). The abnormal expression of circRNA slowly promotes changes in miRNA-mRNA expression and gradually leads to the occurrence of chronic diseases.…”
mentioning
confidence: 99%